A regional hydrological model for arid and semi-arid river basins with consideration of irrigation. (November 2022) - Jiang, Cong; Parteli, Eric J.R.; Xia, Qian; Yin, Xin; Shao, Yaping
Abstract: We develop a regional hydrological model that applies to arid and semi-arid regions, by explicitly considering the effect of irrigation on the hydrological processes. A new irrigation module is here integrated into the recently introduced Atmospheric and Hydrological Modelling System (AHMS) for the quantitative assessment of basin-scale hydrological response to climate change and the impact of anthropogenic activities on water resources. The land surface, channel routing and groundwater modules of the AHMS are extended here to incorporate the new module. We then apply the model to simulating the hydrological processes in the Yellow River Basin, an arid and semi-arid region where irrigation constitutes the most important source of water use. The model is calibrated and validated using in-situ and remote sensing observations. This study demonstrates the capability of the AHMS for regional hydrological modelling in arid and semi-arid basins where irrigation profoundly influences the water balance. Highlights: We introduce a new irrigation model for regional hydrological simulations. Our irrigation model considers off-stream water flux over long distances from the river to irrigation districts. We explicitly model the actual irrigation amount from soil moisture deficit, water availability and irrigation fraction. GRACE data are considered in the model verification and assessment. Our irrigation model provides a useful tool for hydrological modelling in arid and semi-arid basins.